PENGEMBANGAN LKPD IPAS BERBASIS MODEL PROBLEM BASED LEARNING (PBL) UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN 1 SEKARTEJA - Buhairatul Amni; Muhammad Husni; Yul Alfian Hadi; Husnul Mukti (STKIP Subang, 2024)
This study aims to develop teaching materials for LKPD IPAs Based on the ProblemBased Learning (PBL) Model on IPAs content for fourth grade students of SDN 1Sekarteja. This study is a type of Research and Development (R&D) research withreference to the ADDIE (Analysis, Design, Development, Implementation,Evaluation) development model. The instruments in this development research usevalidation sheets and student response questionnaires. The validation results frommedia experts with a total score of 72 which is in the range of X> 67.08 so that itcan be categorized as